The risk factors of deep vein thrombosis in pregnancy intensive care unit, Alzahra Hospital in Tabriz, 2019 - Fatemeh Mallah; Nafiseh Sheghaghi Ilkhchi; Dara Alvandfar (Mashhad University of Medical Sciences, 2021)
Introduction: Deep vein thrombosis is a fatal complication during pregnancy. Lack of accurate knowledge of the epidemiology of this dangerous complication will lead to its concealment, followed by later diagnostic and ancillary measures; therefore, this study was performed with aim to epidemiological study of deep vein thrombosis in pregnant women admitted to the intensive care unit. Methods: This descriptive-analytical study was performed in 2019 on 49 women admitted to the intensive care unit (before pregnancy and postpartum) in Taleghani and Al-Zahra hospitals (Tabriz Medical Sciences). Venous thrombosis information was recorded in the form related to the causes of deep vein thrombosis. Data were analyzed by SPSS statistical software (version 22) and Chi-square test. P<0.05 was considered statistically significant. Results: Smoking (P=0.036), obesity (P=0.011), diabetes (P=0.035), heart disease (P=0.033), hypertension (P=0.011), multiple (P=0.029), thrombocytopenia (P= 0.048), prenatal bleeding (P=0.041), blood transfusion during pregnancy (P=0.049), history of surgery in recent three months (P=0.048), amniotic infection (P=0.039) were the factors affecting deep vein thrombosis. Conclusion: Smoking, obesity, diabetes, heart disease, hypertension, multiple births, thrombocytopenia, prenatal bleeding, blood transfusion during pregnancy, history of surgery in recent 3 months and amniotic infection are the risk factors for deep vein thrombosis in women admitted to the intensive care unit. Therefore, attention and care is essential in people with risk factors mentioned in pregnant women.